Review in Acne Vulgaris along with its treatment - Palange, Anushka; Barge, Mrudula; Naikwadi, Nishigandha (Asian Journal of Pharmaceutical Research and Development, 2024)
Acne is a prevalent inflammatory skin condition that impacts the skin’s sebaceous units. Both significant psychological effects and severe skin scarring may result from it for the patient.Acne is caused by four well-known pathological factors, which are the focus of acnetreatment. Several treatment options are covered in this review, including topical (retinoids and antibiotics) and systemic (retinoids, hormones, and antibiotics) treatments. Complementary and alternative medicine (CAM) was also suggested as a potential acne treatment since the general public has been expressing interest in safer and more natural treatment options. There is also mention of the application of physical therapies such cryoslush therapy, electrocauterization, comedone extraction, cryotherapy, intralesional corticosteroids, and optical treatments. Considerable study has been done on acne’s underlying causes and available therapies.However, new therapeutic approaches are required since Propionibacterium acnes is becoming more resistant to the drugs that are already accessible. Researchers must also look at these therapy options more thoroughly because there is insufficient data to support the effectiveness of complementary and alternative medicine.